Dual Dynamic Network Polymer Reinforced Carbon Nanotube Foam With Rapid Self‐Healing and Reversible Cycling Capabilities - Huitao Yu; Can Chen; Yanshuai Duan; Linghang Wang; Mengmeng Qin; Wei Feng (SmartMat)
ABSTRACT The structural damage of carbon–polymer composites is a significant factor limiting their development and stable application. To solve this problem, polymers with fast self‐healing and recyclability were first obtained by introducing dynamic polymer chain segments in different proportions. When the molar ratio of H‐linked 2‐[[(butylamine)carbonyl]oxy]ethyl ester (PBC) and boric acid ester–linked poly(4‐hydroxymethyl) phenylboronic acid (PBA) is 2:1, the highest mechanical strength (2.9 ± 0.2 MPa) and elongation (700%) of the PBC2‐PBA1 were achieved. Subsequently, the hydroxylated modified carbon nanotube foams (CNTF) were used as templates, which were filled with PBC2‐PBA1 via a physical impregnation process to prepare CNTF polymer composites (PBC2‐PBA1/CNTF). When the CNTF content is 13.4 wt%, the composite exhibits high tensile strength of 5.5 MPa, 189% higher than the mechanical strength of PBC2–PBA1. Furthermore, it exhibits the self‐healing properties were by the recovery of tensile strength (100%), thermal conductivity (98.7%), and electrical conductivity (100%) at −20°C~100°C. In addition, the composite materials can be recycled and the reassembled material can restore 100% of its original mechanical properties. Therefore, optimization of molecular structure and modification of phase interfaces are the strategies to produce carbon‐polymer composites with excellent self‐healing and recycling functions.